Finite element modeling of suction anchors under combined loading - Monajemi, H.; Razak, H.A. (2009)
Suction anchors are subjected to inclined, quasi-horizontal or quasi-vertical loadings. The type of the structure and depth of water govern the inclination of the load. Under this load condition, suction anchor experiences a combination of horizontal and vertical translations, and rotation. Therefore the soil's reaction to this load condition can be idealized as horizontal and vertical loadings, together with a moment. The magnitude and combination of the reactions depend on the load inclination, soil property and the point at which the load is applied. The behavior of the suction anchor subjected to the combined V-H-M loading is elaborated in this paper. This is to observe the effects of soil properties on the failure mechanism and ultimate capacity of the foundation. This was achieved by applying the pure horizontal and vertical displacements, and rotation and their combinations to the foundation, on V-H, V-M and H-M spaces and the yield-locus created for each space. The general purpose finite element program DIANA was used for this study. Non-linear analysis was conducted using a simplified elastic-perfectly-plastic model with Von-Mises yield criterion for saturated and consolidated clay. Â© 2009 Elsevier Ltd. All rights reserved.